An illustrative concept solution for future Last-mile Deliveries: A development process focusing on the recipients´ experience of their LMT process - Malmsten, Clara (My University, 2022)
Last-mile deliveries (LMD) are costl\ and account for about 50% of the total deliver\ cost, indicating the importance of it being done as smoothl\ and precisel\ as possible. Δn combination Zith its operational comple[it\, the consumers are placing higher demands on their deliveries as e-commerce becomes more popular and increases \earl\. Recipients require a fle[ible deliver\ solution alloZing them to receive their parcels Zithin a short distance. Toda\, there is generall\ no solution Zhere both of these factors are offered. The aim of this project Zas to develop an illustrative concept solution fulfilling the needs and requirements recipients place on their LMD process. The illustrative concept solution Zas developed Zith the main focus on the recipientȇs needs and requirements. When the final concept Zas chosen, improvements Zere made in order to facilitate the LMD process for both the logistics personnel as Zell as for the postal office personnel. Collected data from intervieZs, focus groups and a questionnaire, performance of tZo empirical ideation sessions and man\ iteration sessions resulted in a final concept. M\ Placed Parcel is a concept solution that can be implemented in toda\ȇs LMD process offering the recipients both high fle[ibilit\ and deliveries Zithin a short distance as parcels are distributed to connection points. M\ Placed Parcel consists of ph\sical products, a digital communication s\stem and s\stem routines.